4 - The Media Struggles in Zambia: The Need for a Unified Policy on Press Freedom - Kenny Makungu (Africa Media Review, 2004)
This paper traces the evolution of the struggles for press freedom in Zambia since the country’s independence. While progress has been made in various fronts, the paper notes that sustaining the gains of the struggles requires continuing pressure on the government from the citizenry and on the political will of government.